‘New Normal’ in a Hospitality with Family Management in Graha Dewata Juwana Hotel - I Gusti Ketut Indra Pranata Darma (Politeknik Pariwisata NHI Bandung, 2021)
The hospitality industry is one part of the world of tourism which plays an important role wherever located. The role of the hospitality industry is not only as a place to stop and rest, but it is a beginning of the economic activities of other industries. The arrival of covid-19 virus in early 2020, no doubt hit all the industrial sectors in the world including the hospitality industry. For almost 3 months, people in the world are forced to live in fear of the covid-9 virus. The World Health Organization (WHO) also called for